2021
DOI: 10.7759/cureus.16405
|View full text |Cite
|
Sign up to set email alerts
|

To Give or Not to Give? Prescribing Antibiotics to the Tonsillectomy Patients in a Tertiary Care Setting

Abstract: IntroductionAdeno-tonsillectomy is one of the most common procedures performed worldwide in pediatric age group. Antibiotics use after tonsillectomy is like any other surgical procedure; and it is thought that the antibiotic use may help to reduce post-operative morbidity. Giving antibiotics in tonsillectomy patients is a common practice for decades but recently there has been a paradigm shift towards not using the antibiotics, especially in the pediatric population. MethodsA prospective study was done on a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This agree with Padia et al [25] who reported that the use of antibiotics (especially oral antibiotics may lead to gastric upsets, nausea, vomiting, and allergic reactions in IV antibiotics) have unwarranted side effects, and disagree with Junaid et al [6] , who found that the patients receiving oral antibiotics did not complain of any drug-related adverse reaction, and relay this on the possibility that most of the patients have been prescribed in the past, multiple antibiotics for their recurrent tonsil infection and hence they tolerated it well.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This agree with Padia et al [25] who reported that the use of antibiotics (especially oral antibiotics may lead to gastric upsets, nausea, vomiting, and allergic reactions in IV antibiotics) have unwarranted side effects, and disagree with Junaid et al [6] , who found that the patients receiving oral antibiotics did not complain of any drug-related adverse reaction, and relay this on the possibility that most of the patients have been prescribed in the past, multiple antibiotics for their recurrent tonsil infection and hence they tolerated it well.…”
Section: Discussionsupporting
confidence: 75%
“…As a result, the issue is still up for debate. Additionally, although subsequent haemorrhage is typically linked to infection and treated with antibiotics in such individuals, it is unknown if there is a causative link and whether the risk is decreased [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Junaid et al reported that regular use of antibiotics in post-tonsillectomy patients does not prevent or reduce postoperative complications. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The main risk factors that may affect haemorrhage rates after CTE will be collected in this study. [9][10][11][12][13][14][15][16][17][18][19][20] Risk factors due to the patient's own condition include, gender, age, body mass index, education status of the primary guardian, date of symptoms onset, parameters of polysomnography, concomitant symptoms other than sleep disorders, history of other systemic diseases, tonsil size, adenoid size, etc. Risk factors due to surgical intervention include surgery date, surgery time, intraoperative blood loss, use of suture haemostasis technique, use of medicine during anaesthesia, brand and model of plasma radiofrequency used in the operation, etc.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation